Perceptual learning of systematic variation in Malaysian English among Libyan EFL learners - Salheen, Dalal Alfadhil Attaher; Yap, Ngee Thai; Mohamad Ali, Afida; Nimehchisalem, Vahid (Universiti Putra Malaysia Press, 2019)
With the ever-increasing population of non-native speakers (NNS) of English around the world, encountering foreign-accented speech (FAS) has become frequent and inevitable, even in an English as a Foreign Language (EFL) teaching and learning context as more and more non-native English teachers are trained and recruited around the world. This study set out to examine the nature and extent of Libyan EFL learners’ perception of Malaysian-accented English as Malaysia is one of the frequent postgraduate study destinations for Libyans. The study also attempts to examine the effect of exposure to Malaysian accented English in a speech intelligibility task. Libyan EFL learners received training with English sentences produced by fifteen Malaysian English speakers for five consecutive days. Sixteen undergraduate students recruited from a public university in Libya completed two intelligibility tasks; one as the pretest and the other as the post-test. The task involved listening to a list of sentences presented to them only once on the computer. While listening to the sentences, participants had to complete a cloze task with a total of 50 missing keywords. On average, the participants performed better in the post-test, as compared with the pretest. The results indicated a statistically significant difference between the pretest and the post-test, and this indicates that Libyan EFL learners could attain better speaker-independent adaptation to the Malaysian English variety when exposed to multiple speakers of the given accent during training. It is, therefore, concluded that perceptual training had a significant effect on the participants’ achievement in speech perceptual learning.